Masters of the planet : the search for our human origins - Tattersall, Ian (Palgrave Macmillan, 2012)
"When homo sapiens made their entrance 100,000 years ago they were confronted by a wide range of other early humans--homo erectus, who walked better and used fire; homo habilis who used tools; and of course the Neanderthals, who were brawny and strong. But shortly after their arrival, something happened that vaulted the species forward and made them the indisputable masters of the planet. This book is devoted to revealing just what that difference is. It explores how the physical traits and cognitive ability of homo sapiens distanced them from the rest of nature. Even more importantly, Masters of the Planet looks at how our early ancestors acquired these superior abilities; it shows that their strange and unprecedented mental facility is not, as most of us were taught, simply a basic competence that was refined over unimaginable eons by natural selection. Instead, it is an emergent capacity that was acquired quite recently and changed the world definitively"--